(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2022)
This paper examines what it means to teach existentially and to write existentially. These are contrasted with teaching existentialism and writing about existentialism which have more in common with the banking method of education. These ideas are then examined for their philosophical and practical dilemmas and paradoxes which are compared and contrasted. Recommendations are made for the nature of teaching existentially and writing existentially.